PENGEMBANGAN MEDIA BOARD GAME MISI PERCAYA DIRI UNTUK MENINGKATKAN RASA PERCAYA DIRI SISWA (RESEARCH AND DEVELOPMENT PADA SISWA KELAS VIII SMPN 10 KOTA SERANG) - Mahya Rianisela; Lenny Wahyuningsih; Bangun Yoga Wibowo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The formulation of the problem in this study is how a board game can be used as a guidance and counseling service medium to improve students’ self-confidence. This study aims to develop the Misi Percaya Diri board game as a guidance and counseling service medium to enhance junior high school students’ self-confidence. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. To determine the feasibility and practicality of the media, the researcher conducted validation tests involving several experts, including media experts, material experts, language experts, and practitioner experts, with the purpose of assessing the feasibility of the product and obtaining feedback before testing it on students. The results showed that the product obtained an average feasibility score of 91% from expert validation, which falls into the “Very Feasible” category. Based on the results of the trial conducted in class VIII of SMPN 10 Kota Serang, the developed product was found to be feasible for use as a guidance and counseling service medium to improve junior high school students’ self-confidence.